Pedagogic Tailoring of a Human Research Ethics Training for Community-Engaged Research With Latinos - Documet, Patricia I.; Louth, William; Smith-Tapia, Ivonne; Jaime, Maria Catrina; Miller, Elizabeth; Taverno Ross, Sharon E. (Health promotion practice, 2022)
Because of the increase in community-engaged research, several human research ethics trainings for laypeople have been developed. We aim to (1) describe the pedagogical tailoring of a research ethics training for laypeople for a research study where promotores—community health workers—delivered an intervention to increase health care access and promote healthy behaviors among Latinos and (2) present results of the application of the training after 4 months in the field. We tailored a previously developed training to Latino community members implementing a research study. Key modifications included (1) translation (2) use of pedagogical tools, such as cooperative learning, role-plays, and inclusion of cultural preferences. One novel addition was to use dialogues that the trainees enacted and then discussed. We evaluated the training with a posttraining survey with eight community liaisons and 13 promotores implementing the intervention, and a focus group with eight promotores, 4 months after working in the field. Trainees said they felt confident obtaining informed consent, felt the dialogues were realistic and helped them remember what they learned, and wanted more feedback from trainers on their performance. Promotores demonstrated the application of ethical principles beyond the training by discussing the possibility of advertising broadly in social media (justice), the risks and benefits of providing community resources to participants (beneficence), and the university’s role in legitimizing their position as promotores (respect). We conclude that a pedagogically tailored ethics research training for laypeople can be successful and that dialogues to be enacted need to be explored further.